The Role of Regional Original Income, Regional Size, and Transfer Funds in Improving Regional Financial Performance - Rahmi Nur Islami; Rudy Bin Ansar; Tengku Putri Azizah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study analyzes the implementation of the regional autonomy system after the transition from a centralized system, focusing on evaluating the financial performance of local governments through aspects of independence, effectiveness, and regional financial growth. The main factors influencing local financial performance are local government size, local own-source revenue (PAD), and transfer fund management. This study offers a new contribution by examining the simultaneous influence of PAD, regional size, and transfer funds on regional financial performance, especially in Tarakan City, which has unique geographical and socioeconomic characteristics. The results of this study provide important insights for local governments in designing more effective and efficient financial management strategies. In addition, these findings are expected to be a reference for policymakers in formulating transfer fund allocation formulas and PAD optimization to improve regional financial performance sustainably. This research method uses a descriptive quantitative approach with a purposive sampling technique. The data used is secondary quantitative data, and the analysis is conducted using multiple linear regression with classical assumption tests. The results show that PAD has a positive effect on regional financial performance, supporting financial independence. In contrast, regional size has a negative effect, reflecting resource management challenges in larger regions. Fund transfers have a positive effect, confirming their role in improving regional financial performance. This research also opens up opportunities for further studies on the relationship between regional financial management and regional economic development.